OPTIMALISASI LITERASI ANAK MELALUI PERPUSTAKAAN DI DESA MONTONG ARE LOMBOK BARAT - Ermiana, Ida; Fauzi, Asri; Nurhasanah, Nurhasanah; Affandi, Lalu Hamdian; Rahmatih, Aisa Nikmah; Setiawan, Heri; Ibrahim, Ibrahim; Wahyuningsih, Baiq Yuni (LPPM Universitas Flores, 2025)
Village libraries play an important role as literacy centres within rural communities. A village library serves as a literacy initiative, bringing reading materials to strategically accessible locations in the community, with the aim of enhancing literacy levels and fostering reading interest. The methods employed in this activity included observation, interviews, and socialisation through a community-based approach that involved residents. The target group consisted of early childhood children, including those who had not yet entered school and those who were already attending school. The results show that the literacy skills of children who visited the village library improved, as reflected in the variety of books borrowed, their ability to engage in dialogue and convey the content of the books, as well as their ability to colour according to the instructions provided in the reading materials. The children’s enthusiasm for diverse reading materials serves as a strong indicator that should be taken into consideration in managing the village library, particularly in continuously providing new and relevant reading books.